A proposed methodology for trip recovery training without a specialized treadmill - Lee, Youngjae; Alexander, Neil B.; Madigan, Michael L. (Frontiers in Sports and Active Living, 2022)
Falls are the leading cause of accidental injuries among adults aged 65 years and older. Perturbation-based balance training is a novel exercise-based fall prevention intervention that has shown promise in reducing falls. Trip recovery training is a form of perturbation-based balance training that targets trip-induced falls. Trip recovery training typically requires the use of a specialized treadmill, the cost of which may present a barrier for use in some settings. The goal of this paper is to present a methodology for trip recovery training that does not require a specialized treadmill. A trial is planned in the near future to evaluate its effectiveness. If effective, non-treadmill trip recovery training could provide a lower cost method of perturbation-based balance training, and facilitate greater implementation outside of the research environment.